Earlier the Patients Entering Into Prenatal Care, Higher the Cesarean Rates: Analysis of 17.035 Cases - Pinar Calis; Burak Gultekin; Fatma Doga Ocal; Gurcan Akgul; Afra Alkan (Gynecology Obstetrics & Reproductive Medicine)
Objective: To analyze whether the time the patients entering into prenatal care affects the route of delivery, maternal, and fetal outcomes.